Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/1759091418781889
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Abnormalities in Substantia Nigra Lipids in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a neurodegenerative movement disorder involving the selective loss of dopamine-producing neurons in the substantia nigra (SN). Differences in disease presentation, prevalence, and age of onset have been reported between males and females with PD. The content and composition of the major glycosphingolipids, phospholipids, and cholesterol were evaluated in the SN from 12 PD subjects and in 18 age-matched, neurologically normal controls. Total SN ganglioside sialic acid content and wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
79
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 58 publications
17
79
2
1
Order By: Relevance
“…The ganglioside mean content in the brain from seven Parkinson's disease male with age ranging from 67 to 95 was found to be reduced by 22% compared to the brain content of 12 healthy controls with the same age. No difference was found between control and Parkinson's disease females [30].…”
Section: Gm1 Of Neuronal Plasma Membrane In the Central Nervous Systementioning
confidence: 69%
“…The ganglioside mean content in the brain from seven Parkinson's disease male with age ranging from 67 to 95 was found to be reduced by 22% compared to the brain content of 12 healthy controls with the same age. No difference was found between control and Parkinson's disease females [30].…”
Section: Gm1 Of Neuronal Plasma Membrane In the Central Nervous Systementioning
confidence: 69%
“…Interestingly, neuronal loss in male SNc is accompanied by a significant reduction in total ganglioside content, especially neuronal-or synaptic-enriched gangliosides GD1a and GT1b. No significant abnormalities were found in female PD subjects [93]. Accordingly, it has been demonstrated that estradiol acts as homeostatic modulator of lipid rafts, thus preserving lipid balance in neuronal membrane microdomains [94].…”
Section: Dopaminergic Neurodegenerationmentioning
confidence: 91%
“…Reduced expression of GM1, GD1a, and GD1b were reported in the occipital cortex of PD patients using HPTLC [ 19 ]. Using HPTLC, we have also recently described significant decreases in GD1a, GD1b, and GT1b in SN from male PD patients, along with a smaller magnitude decrease in GM1 that did not reach statistical significance [ 20 ]. In contrast, we found no significant changes in levels of GM3, GM2, or GD3 in PD SN.…”
Section: Introductionmentioning
confidence: 99%